Co(OH)F@CoP/CC core-shell nanoarrays for high-performance supercapacitors. (1st November 2022) - Liu, Didi; Li, Shuran; He, Yezeng; Liu, Chao; Li, Qinglong; Sui, Yanwei; Qi, Jiqiu; Zhang, Ping; Chen, Changjiu; Chen, Zheng; Liu, Sida
Abstract: The transition metal phosphides have drawn wide attention as positive material used in supercapacitors owing to the excellent conductivity and electrochemical activity. In this work, the novel composite Co( OH )F@CoP core-shell nanoarrays, used as electrode material for supercapacitors, was synthesized on conductive carbon cloth (CC) through the hydrothermal method and phosphating process. The specific capacitance of Co( OH )F@CoP/CC is 654mC cm −2 at 1 mA·cm −2, and maintains long-life cycling stability of 71.34 % retention after 10, 000 cycles at 10 mA·cm −2 in a three electrode system. Furthermore, a two-electrode system assembled by Co( OH )F@CoP and reduced graphene oxide (RGO) exhibits performance with energy density of 17.933 Wh kg −1 at power density of 800 W kg −1 . These results proved that the Co( OH )F@CoP composite is an advanced electrode material for the supercapacitors. Highlights: Co( OH )F@CoP/CC core-shell nanoarrays were successfully prepared. The Co( OH )F@CoP/CC electrode exhibits superior specific capacitance of 654mC cm −2 at 1 mA·cm −2 . The asymmetric supercapacitor possess excellent energy density and cycling stability.